Possession : a novel - Rule, Ann. (New York : Pocket Star Books, 1997)
After her police-officer husband is killed in a terrible accident while they are wilderness camping, Joanne Lindstrom must depend for her survival on violent, cunning Duane Demich, who may have planned the accident
Originally published: New York : Norton, 1983.